Heterogeneous effects of sleep and psychological health on pregnancy outcomes in donor insemination: a prospective cohort study - Changsha Yin; Yan Wang; Yan Pu; Yuyang Wang; Biru Luo (Frontiers in Public Health, 2026)
Objective To investigate the impact of sleep quality, anxiety, depression and somatic symptom burden on pregnancy outcomes among patients receiving donor-sperm assisted reproduction, and to explore heterogeneous associations across IVF/ICSI-D and IUI-D subgroups. Methods A prospective cohort study was conducted at the Reproductive Center of West China Second University Hospital, Sichuan University. From June 2020 to May 2024, 758 consecutive patients undergoing donor insemination-assisted reproduction were enrolled, including 234 undergoing IVF/ICSI-D and 516 undergoing IUI-D. Somatic symptom burden, anxiety, depression, and sleep quality were assessed using the Patient Health Questionnaire-15 (PHQ-15), Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), and Pittsburgh Sleep Quality Index (PSQI), respectively. Baseline demographic characteristics and infertility-related variables were systematically recorded. Univariate screening followed by fully adjusted multivariable logistic regression and sensitivity analysis excluding educational attainment were performed to identify independent predictors of multiple pregnancy endpoints. Results In the IVF/ICSI-D subgroup, higher PSQI scores (indicating poorer sleep) displayed independent correlative links to lower odds of clinical pregnancy (OR = 0.827, p = 0.012) and live birth (OR = 0.850, p = 0.031); higher sleep scores were also correlated with reduced odds of preterm delivery (OR = 0.733, p = 0.047). For the IUI-D cohort, elevated sleep scores showed a positive correlative association with miscarriage odds (OR = 1.976, p = 0.041). Notably, mild anxiety was observed in 97% of IVF/ICSI-D participants, and rising anxiety scores were positively correlated with higher odds of live birth (OR = 1.185, p = 0.043) and cesarean delivery (OR = 1.192, p = 0.029). Conclusion Sleep quality displays correlative predictive links to pregnancy outcomes among donor insemination recipients, with distinct correlative patterns observed across different ART modalities. Mild anxiety exhibits a positive correlative association with favourable live birth rates within the IVF/ICSI-D subgroup, alongside a correlative link to higher cesarean delivery prevalence. Our observational associations support the clinical value of routine sleep screening and individualized psychological support for this patient cohort.